Cyclic plasticity and thermomechanical alleviation in titanium alloys. (November 2020) - Xu, Yilun; Fox, Kate; Rugg, David; Dunne, Fionn P.E.
Abstract: Cyclic behaviour of titanium alloy IMI834 has been investigated with a new thermo-mechanically coupled discrete dislocation plasticity formulation, integrated with experimental observation. The mechanistic basis of the cyclic loading dependence is shown to be the establishment of dislocation pileups and back stress development such that on partial unloading, reversed strain occurs by thermally-activated dislocation escape and reverse glide during a secondary stress hold. Anomalous cyclic strain accumulation in both isothermal and anisothermal stress-loaded alloy IMI834 is explained by the reversed straining and dislocation structure re-arrangement mechanisms. The mechanisms also provide the underpinning explanation for the beneficial effect of elevated temperature excursions in diminishing cyclic creep accumulation and hence reducing dwell fatigue sensitivity in titanium alloys by thermal alleviation. Highlights: A new thermo-mechanically coupled discrete dislocation plasticity (DDP) formulation has been developed. Anomalous cyclic strain accumulation in both isothermal and anisothermal reversed loading is observed experimentally. Unusual behaviour explained in terms of negative strain due to dislocation glide and thermally-activated escape. The mechanisms also provide the underpinning explanation for the beneficial effect of elevated temperature excursions.